Pre- and postsynaptic changes in the neuromuscular junction in dystrophic mice - Pratt, Stephen J.; Valencia, Ana P.; Le, Gloribel K.; Shah, Sameer B.; Lovering, Richard M. (Frontiers in Physiology, 2015)
Duchenne muscular dystrophy (DMD) is a devastating neuromuscular disease in which weakness, increased susceptibility to muscle injury, and inadequate repair appear to underlie the pathology. While most attention has focused within the muscle fiber, we recently demonstrated in mdx mice (murine model for DMD) significant morphologic alterations at the motor endplate of the neuromuscular junction (NMJ) and corresponding NMJ transmission failure after injury. Here we extend these initial observations at the motor endplate to gain insight into the pre- vs. postsynaptic morphology, as well as the subsynaptic nuclei in healthy (WT) versus mdx mice. We quantified the discontinuity and branching of the terminal nerve in adult mice. We report mdx- and age-dependent changes for discontinuity and an increase in branching when compared to WT. To examine mdx- and age-dependent changes in the relative localization of pre- and postsynaptic structures, we calculated NMJ occupancy, defined as the ratio of the footprint occupied by presynaptic vesicles versus that of the underlying motor endplate. The normally congruent coupling between presynaptic and postsynaptic morphology was altered in mdx mice, independent of age. Finally we found an almost two-fold increase in the number of nuclei and an increase in density (nuclei/area) of nuclei underlying the NMJ. These outcomes suggest substantial remodeling of the NMJ during dystrophic progression. This remodeling reflects plasticity in both pre- and postsynaptic contributors to NMJ structure, and thus perhaps also NM transmission and muscle function.